PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS DI CV. JAYA ABADI BANDUNG - Ratnanto Aditiarno; Phani Putri Valentina; Karyadi (POLITEKNIK PIKSI GANESHA, 2022)
This study aims to determine the effect of capital structure on profitability in CV. Jaya Abadi. The research method used is descriptive quantitative method. The data used is primary data in the form of financial statements CV. Jaya Abadi. The hypothesis testing technique uses Simple Linear Regression with the help of SPSS 25. The results of this study indicate that the capital structure as measured by Debt to Equity Ratio (DER) has no effect on profitability as measured by Return on Equity (ROE) in CV. Jaya Abadi. This result is probably caused by the not yet optimal capital structure in CV. Jaya Abadi.